Impact of military metallurgical plant wastes on the population's health risk - Pawełczyk, Adam; Božek, František; Grabas, Kazimierz (Chemosphere, 2016)
This paper presents the results of water, soil and air analyses taken in the vicinity of a former ferrochromium metallurgical plant. In the past, the area was used for the disposal of waste materials containing smelter slag, dust and other waste products from the manufacture of ferrochromium alloys for the army. Recently, production was abandoned and a project aimed at the liquidation of the dump has been initiated. The project concentrates on the recovery of chromium remains and the utilization of the leftover material as a road construction aggregate. Based on the analyses of ground water, soil and air, a health risk caused by environmental pollution with chromium, especially with Cr(VI), was determined for residential and occupational scenarios. It was found that the level of chromium emissions to the environment constitutes a potential danger of toxic and carcinogenic cases in humans exposed to the emission in the affected area. An increased level in the hazard quotient has been observed in the case of occupational activities. As far as the mutagenic effects are concerned, the occupational inhalation exposure was found to be very high, which may raise extreme concern about carcinogenic risk.
Keywords: dospělí; Chromium Alloys; Chromium; Government; hodnocení rizik; konstrukční materiály; dítě; Adult; Industrial Waste; lidé; Occupational Exposure; Health risk; průmyslový odpad; Risk Assessment; inhalační expozice; hutnictví; Environment pollution; voda; Humans; Metallurgy; slitiny chromu; Water; Health hazard; chrom; prach; pracovní expozice; Environmental Pollutants; Dust; Construction Materials; Child; látky znečišťující životní prostředí; Poland; vláda; Inhalation Exposure; Polsko